2017
DOI: 10.14338/ijpt-17-00003.1
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Radiation Therapy for Treatment of Refractory Merkel Cell Carcinoma

Abstract: We describe the first reported use of neutron radiation therapy for successful palliation of treatment refractory Merkel cell carcinoma. The patient was a 78-year-old man with Merkel cell carcinoma involving the scalp and bilateral cervical lymph nodes. The extensive coalescing scalp lesions were locally destructive, painful, and highly detrimental to his overall quality of life, and he had previously progressed through 3 courses of conventional x-ray-based radiation therapy and multiple immunotherapy regimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…At the University of Washington (UW), we continue to find fast neutron therapy clinically more useful and effective in the treatment of patients at high risk for local recurrences in both curative and palliative settings (Laramore et al 1989a, 1989b, Douglas et al 1999, Schwartz et al 2001, Liao et al 2014, Davis et al 2016. Macomber et al (2017) recently reported an especially striking example of the use of fast neutron therapy in the treatment of recurrent Merkel cell carcinoma (MCC). After the disease progressed through three courses of photon and electron treatments (total dose of up to 91.2 Gy in equivalent 2 Gy fractions to the scalp), the patient had a complete clinical and radiologic response two months after a neutron treatment of 18 Gy in 12 daily fractions.…”
Section: Introductionmentioning
confidence: 99%
“…At the University of Washington (UW), we continue to find fast neutron therapy clinically more useful and effective in the treatment of patients at high risk for local recurrences in both curative and palliative settings (Laramore et al 1989a, 1989b, Douglas et al 1999, Schwartz et al 2001, Liao et al 2014, Davis et al 2016. Macomber et al (2017) recently reported an especially striking example of the use of fast neutron therapy in the treatment of recurrent Merkel cell carcinoma (MCC). After the disease progressed through three courses of photon and electron treatments (total dose of up to 91.2 Gy in equivalent 2 Gy fractions to the scalp), the patient had a complete clinical and radiologic response two months after a neutron treatment of 18 Gy in 12 daily fractions.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in Macomber et al [18], a 78-year-old white male with no history of immunosuppression had recurrent MCC disease following intralesional and systemic anti-PD1 immunotherapy (pembrolizumab) with disease progression inside and outside prior low LET radiation therapy fields. The patient was treated with definitive doses of fractionated NRT for the fungating gross disease on the central scalp to a total dose of 18 Gy neutron in 12 fractions (1.5 Gy per day, 4 days per week), the bilateral parotid/cervical lymph nodal disease (18 Gy neutron in 10 fractions), and frontal scalp lesions (16 Gy neutrons in 8 fractions).…”
Section: Patient B: Update On Patient With Progression On Anti-pd1 Immentioning
confidence: 61%
“…The exact underlying mechanism(s) and triggers to reproducibly generate this effect remain to be elucidated. To gain insight into the clinical significance of short-course NRT as it relates to in-field and out-of-field organ at risk (OAR) toxicity, updated dosimetry and clinical observations for a previously reported patient case by Macomber et al [18] is also presented (patient B). This case series illustrates the use of NRT in combination with immunotherapy to achieve potentially durable clinical responses in patients who had exhausted other treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Macomber et al [82] applied FNT for refractory cutaneous Merkel cell carcinoma in a patient with a previous treatment failure; LC was achieved with 18 Gy in 12 fractions and lasted for 2 years. Schaub et al [83] presented 2 promising observations of Merkel cell carcinoma treated with FNT, noting a potential relationship between high-LET neutron beam irradiation and elevated immune response.…”
Section: Clinical Experiencementioning
confidence: 99%